IMPLIKASI PROGRAM BANTUAN PANGAN NON TUNAI PADA PENGELUARAN KONSUMSI RUMAH TANGGA MISKIN.: Studi Kasus di Kecamatan Bojongloa Kaler Kota Bandung. - Fajar Eryanto Septiawan; Silvia Maulidina (Jurnal Riset Ilmu Ekonomi, 2021)
This study aims to reveal the extent to which the program has been successful, especially if it is related to the consumption costs of the poor which will be described through the relationship between non-cash food assistance and food and non-food consumption expenditures. The research was carried out with a quantitative descriptive method, where the data related to none other than the results of a case study survey in the District of Bojongloa Kaler. The number of respondents in this study amounted to 100 who were determined by cluster random sampling technique. Furthermore, the data were analyzed using normality test and canonical correlation. The results of data processing illustrate that there is a correlation between non-cash food assistance and food and non-food consumption expenditures, in which there is a relationship between non-cash food assistance and food consumption expenditure. Moreover, the strong correlation between the dependent and other independent variables can be reflected in the variable rice consumption expenditure and the amount of rice per capita.